2010
DOI: 10.1186/1471-2318-10-36
|View full text |Cite
|
Sign up to set email alerts
|

The factorial structure of the mini mental state examination (MMSE) in Japanese dementia patients

Abstract: BackgroundThe Mini-Mental State Examination (MMSE) is one of the most commonly used instruments in the evaluation of global cognitive status. Few studies have investigated the relationship among its components in terms of factorial structure in Japanese individuals suffering from dementia. The aims of this study were: 1) to analyze the factorial structure of MMSE in Japanese dementia patients, 2) to clarify the MMSE static structure in identifying different cognitive profiles and understanding how these profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 22 publications
3
66
0
4
Order By: Relevance
“…It has been reported that these MMSE domains are not affected by impairment of the hippocampus 26) . Therefore, we assume that the cognitive dysfunction resulting from arterial stiffness is not attributed to dysfunction of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that these MMSE domains are not affected by impairment of the hippocampus 26) . Therefore, we assume that the cognitive dysfunction resulting from arterial stiffness is not attributed to dysfunction of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…The test can be used to distinguish between older adults with and without neuropsychiatric disorders and as a follow up test to measure the progress of the disorder across time (Cacho et al, 2010). MMSE asks questions that assess 5 areas of cognitive functioning (i.e., orientation, immediate memory, attention/concentration, delayed recall, language) (Shigemori, Ohgi, Okuyama, Shimura, & Schneider, 2010). The results of a few surveys indicate that the MSSE has become the most commonly used cognitive test by the health professionals such that approximately 9 out of 10 experts have reported using the test predominantly (Cacho et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several other investigators evaluated the factorial structure of the MMSE in different stages of dementia, but there is no detailed data about the changes in factorial structure of the MMSE in follow-up period (15)(16)(17).…”
Section: Introductionmentioning
confidence: 98%